Fitoquímica e avaliação do efeito sobre a liberação de citocinas pró-inflamatórias de espécies do gênero Baccharis. - Alessandra Caroline Montes Frade (2020)
Medicinal plants are an important source of bioactive compounds, especially the genus Baccharis (Asteraceae), which is native to the Americas, has about 500 species, 167 of which are found in Brazil. This genus stands out for its popular use as an anti-inflammatory and the treatment of gastrointestinal diseases, and its therapeutic actions are attributed to high concentrations of special metabolites such as flavonoids and terpenes. Thus, the genus Baccharis is considered a promising source of new compounds for the treatment of inflammatory diseasessuch as gouty rheumatoid and arthritis. In this context, the study of the potential in vitro anti-inflammatory activity of species of this genus and the biomonitoring fractionation of B. calvescens was carried out. Twenty samples of 13 Baccharis species were collected in different regions of the state of Minas Gerais, which resulted in the production of 34 hydroethanolic extracts. After analyzing the chromatographic profiles, 13 extracts were selected to evaluate the effect on the release of the pro-inflammatory mediators TNF and IL-1β in THP-1 cells stimulated by LPS in vitro. The leaf extract of B. calvescens showed a significant reduction of the release of the cytokine IL-1β at a concentration of 20 μg / mL. Fractionation by partition between immiscible solvents of the active extract resulted in the active fraction dichloromethane (DCM), which was refracted into DCM1, and DCM2, the latter being rich in phenolic compounds. The fractions obtained were active and reduced the release of the pro-inflammatory cytokines TNF and IL-1β, with the DCM1 fraction being more active than the DCM2, suggesting that non-phenolic constituents have greater activity than phenolics. Through chromatographic (preparative scale HPLC) and spectroscopic techniques (UV, UPLC-ESI-MS, and NMR), two flavones of the DCM2 fraction, cirsimaritin and genkwanina, were isolated and identified, in addition to being putatively identified by UPLC-ESI-MS o 3,5-O-Dicafeoilquin, apigenin, and naringenin, in the hydroethanolic extract of leaves of B. calvescens. The scarcity of phytochemical studies of species of the genus Baccharis in the literature corroborates the importance of this study, which presented unprecedented results of the biological activity and chemical composition of B. calvescens.